Kerjasama bagi hasil ayam potong untuk meningkatkan kesejahteraan bagi pelaku usaha - Mailani, Robit Altom; Himmati, Risdiana (Nur Science Institute, 2022)
Chicken farming is a form of agribusiness that is capital intensive. Broiler chicken is one of the farms if it is developed to have good prospects. Businesses in the field of animal husbandry in the form of broiler cultivation can establish partnerships. A partnership is a form of cooperation that applies profit sharing. The broiler cooperation program aims to establish mutually beneficial and reinforcing business cooperation and mutual trust between farmers and the core party (business partners or investors). Qualitative analysis was used in this study with a descriptive qualitative model. The study results indicate that the system is a partnership cooperation system, with farmers as plasma following the policy from its core (the investors). The policy on delivery issues already exists. Marketing has been regulated by the core party so that, in this case, the breeder only takes care of it. Profit sharing in partnership applies to an agreement where the nucleus already gives a benchmark price.